On some commutative invariants of modules over minimax nilpotent groups - Tushev, A.V. (Доповіді НАН України, 2022)
In the paper we introduce a finite system of invariants for modules over minimax nilpotent groups which consists of
classes of equivalent prime ideals of the group algebra of an Abelian minimax group. In particuly, introduced system
of invariants allows to study the structure of a minimax nilpotent group N acted by a group of operators G such that
N has injective modules which are stabilized by the group of operators G. У статті введено скінченну множину інваріантів для модулів над мінімаксними нільпотентними групами,
що складається з класів еквівалентних простих ідеалів групової алгебри абелевої мінімаксної групи. Введена множина інваріантів дає змогу, зокрема, вивчати будову мінімаксної нільпотентної групи N, на якій
діє група операторів G, причому N має ін’єктивні модулі, які стабілізуються групою операторів G.